Arise Again, O India - Francois Gautier; GAUTIER (Francois) (New Delhi: Har Anand Publications Pvt Ltd, 2000)
The West has lost the truth. We have lost the Great Sense, the meaning of our evolution, of why so much suffering, why dying, why getting born, why this earth, who are we, what is the soul, what is reincarnation, where is the ultimate truth about the universe... But India has kept this truth. India has preserved it through seven millennium of pitfalls, of genocides and attempts at throttling her santanam dharma. And this will be India's gift to this planet during the next century: to restore to the world its true sense. to recharge humanity with the real meaning and spirit of life. India will become the spiritual leader of the world, as India$1 (Bs Great Sage, Sri Aurobindo, had predicted nearly a century ago : "It is this religion that I am raising-up before the world, it is this that I have perfected and developed through the Rishis, saints, and Avatars, and now it is going forth to do my work among the nations. I am raising forth this nation to send forth my word...When therefore it is said that India shall rise, it is the Santana Dharma that shall rise, it is the Santana Dharma that shall be great. When it is said that India shall expand and extend herself, it is the Santana Dharma that shall expand and extend itself over the world. It is for the Dharma and by the Dharma that India exists". s
Keywords: Indian History; Hindus; Vedas; Muslim Conquests; Federalism